Endoscopic sphincterotomy for bile duct stones: an institutional review of 272 patients. - Bickerstaff, K; Berry, A; Chapman, R; Britton, J (1989)
The results of the first 283 endoscopic sphincterotomies (ES) attempted in Oxford for bile duct stones are described. Endoscopic sphincterotomy was achieved in 272 patients (96%) and complete duct clearance was achieved in 88% of these patients; an overall success rate of 85%. Complications occurred in 26 patients (10%), five of whom required an emergency laparotomy. Eight patients died within 30 days of ES but only two deaths were attributed directly to the procedure. Although the sphincterotomies were performed by several endoscopists in varying stages of training, the results are similar to those from other large reports. In the last year of the study (1987), 58 patients were referred from within the Oxfordshire District which suggests an annual demand for ES for bile duct stones of 11 patients per 100,000 of population.